2015
DOI: 10.1002/pssb.201552668
|View full text |Cite
|
Sign up to set email alerts
|

Electric field dependences of Curie and Néel phase transition temperatures in magnetoelectric relaxor multiferroic Pb(Fe0.5 Ta0.5 )O3 crystals seen via acoustic emission

Abstract: Pb(Fe0.5Ta0.5)O3 magnetic and ferroelectric relaxor multiferroic crystals have been studied under both temperature and dc external electric field conditions by means of acoustic emission technique. All the characteristic relaxor points as Burns Td ≈ 610 K and intermediate T* ≈ 500 K temperatures, as well as both Curie ferroelectric cubic‐tetragonal Tc1 ≈ 259 K and tetragonal–monoclinic Tc2 ≈ 201 K structural and Néel antiferromagnetic–paramagnetic TN ≈ 187 K phase transitions have been successfully detected. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 70 publications
1
6
0
1
Order By: Relevance
“…The dependence of T m on small dc external electric fields, E , is well established and exhibits a nonlinear behavior: initially it decreases, reaches a minimum at some small threshold electric field, E th , and then starts to increase similarly as T c for the second‐order phase transitions in the ordered FEs, as E increases. The origin of such a nonlinear behavior of T m , reliably established in some RFEs , and even for T c in BaTiO 3 , which for a long time was recognized as an ordered FE, was concluded to be a competition between RFs and E when affecting the PNRs .…”
Section: Introductionmentioning
confidence: 93%
“…The dependence of T m on small dc external electric fields, E , is well established and exhibits a nonlinear behavior: initially it decreases, reaches a minimum at some small threshold electric field, E th , and then starts to increase similarly as T c for the second‐order phase transitions in the ordered FEs, as E increases. The origin of such a nonlinear behavior of T m , reliably established in some RFEs , and even for T c in BaTiO 3 , which for a long time was recognized as an ordered FE, was concluded to be a competition between RFs and E when affecting the PNRs .…”
Section: Introductionmentioning
confidence: 93%
“…Calorimetric, birefringence, dielectric, ultrasonic, and acoustic emission studies of PFN and PFT ceramics and single crystals confirmed the presence of the M‐T‐C phase transition sequence. In addition, dielectric studies of single crystals and good quality ceramics (synthesized from mechanically activated powders and by a hot‐pressing method) undoubtedly pointed to the diffuse nature of the ferroelectric T‐C phase transition .…”
Section: Introductionmentioning
confidence: 76%
“…Due to very close lattice parameters and the same iron populations, the Fe 3+ ions create nearly identical magnetic subsystems in PbFe 0.5 Nb 0.5 O 3 and PbFe 0.5 Ta 0.5 O 3 , which undergo the same sequence of two magnetic transitions from the paramagnetic phase to the antiferromagnetic (AFM) one at Neel temperature T N ≈ 150 K and then to the spin‐glass (SG) state at approximately 10 K . There are two models of the SG and AFM states coexistence below 10 K proposed.…”
Section: Introductionmentioning
confidence: 99%
“…The value of the maximum dielectric constant  m could reach above 10,000. The relation between the T m and frequency could be described by V-F function 类似地, 还存在纳米尺度的短程磁有序(NMR) 材料, 其磁性介于长程磁有序材料(铁磁体、亚铁磁 体和反铁磁体)和顺磁材料之间。科学家把短程磁有 序为主的材料称为弛豫铁磁体 [18][19] 。通常采用自旋 玻璃态解释弛豫铁磁体的磁性。在弛豫铁磁体中, 电子的自旋不再统一排列, 而是随机取向, 这种随 机取向不再随时间的改变而变化, 即存在空间坐标 上的"无序"和时间坐标上的"有序"(图 2)。与之 相应, 材料表现出一些新奇的物理效应。 比如, 其交 流磁化率与温度曲线在玻璃态转变温度 T g 附近表 现出异常峰, 并且该异常峰与频率明显相关, 可以 通过 V-F 方程来描述; 在很低的外加直流磁场作用 下, 该异常峰就可被抹平。再比如, 在带场冷却 FC 和零场冷却 ZFC 两种测量条件下, 磁化率在 T g 以下 表现出明显的背离。 [12] 。自由能表示如下: [20][21][22] 。而对于 B 晶格位铁磁活性离子 (Fe 3+ )与铁电活性离子比例为 1 : 1 的 PbFe 1/2 Nb 1/2 O 3 和 PbFe 1/2 Ta 1/2 O 3 , 铁电序基本以长程有序为主, 铁 电结构为四方(空间群 P4mm)相, 后者居里点低于 室温 [23][24][25][26][27] [31] Fig. 3 Schematic representation of Fe 3+ spins arrangement for PbFe 2/3 W 1/3 O 3 , The frustrated Fe 3+ spins appear in AFM sublattices [31] 2007 年, Levstik 研究组 [32] 发现, 在 Increase of the magnetic field H leads to decrease in P r .…”
Section: 弛豫多铁性基本理论unclassified
“…P r is nearly zero when H reaches 0.5 T. This effect disappears after magnetic field being removed. Correspondingly, the anomaly peak of the imaginary part for dielectric constant shifts to the low frequency side with H increasing, which reveals the increase of the relaxation time 的, 通过 Landau-Devonshire 理论, 确定 PNR 的尺寸 为 7~11 nm。 在 BiFeO 3 中引入 BaTiO 3 , 可以形成 BiFeO 3 -BaTiO 3 固溶体系。 研究发现, 随着 BiFeO 3 含量增加, 该体系存在铁电-弛豫转变, 可以表现出弛豫铁电 态和亚铁磁性的共存 [46][47][48][49] 。 该体系三方-准立方相界 附近的 0.67BiFeO 3 -0.33BaTiO 3 以单晶形式存在时, 则表现出更加丰富的磁电性质, 通过中子漫散射实 验, 日本研究者证实了该单晶在 600 K 附近存在 8 nm 左右的 PNR(图 6) [50] 。随着温度上升, PNR 变小, 在 800 K 附近 PNR 消失。此外, 该单晶表现出超顺磁 [31] Ferroelectric relaxor T m = 210 K @0.1 MHz T f = 164 K Anti-ferromagnetic T N = 350 K Magnetic glass state T g = 10 K PbFe 0.5 Nb 0.5 O 3 ceramics [23,29] Ferroelectric T m =373 K Anti-ferromagnetic T N = 153 K Magnetic glass state T g = 10.6 K PbFe 0.5 Ta 0.5 O 3 ceramics [27,30] Ferroelectric T m = 259 K Anti-ferromagnetic T N = 153 K Magnetic glass state T g < 10 K 0.8PbFe 1/2 Nb 1/2 O 3 -0.2PbMg 1/2 W 1/2 O 3 ceramics [32] Ferroelectric relaxor T m = 280 K @0.1 MHz T f = 245 K Magnetic glass state T g = 25K Pb(Fe 0.66 W 0.33 ) 0.8 Ti 0.2 O 3 thin films [33] Ferroelectric relaxor T m = 350 K @ 10 kHz T f = 238 K Ferrimagnetic Pb(Fe 0.66 W 0.33 ) 0.2 (Zr 0.53 Ti 0.47 ) 0.8 O 3 thin film [36] Ferroelectric relaxor T m < 600 K @ 1 MHz Ferrimagnetic Pb(Zr 0.53 Ti 0.47 ) 0.60 (Fe 0.5 Ta 0 . 5 ) 0.4 O 3 thin films [37] Ferroelectric relaxor T m = 390 K @1 MHz T f = 305 K Ferrimagnetic 图 5 基于弛豫多铁性材料的多态存储器 Fig.…”
Section: 弛豫多铁性基本理论mentioning
confidence: 99%